Purifying the land of the pure : a history of Pakistan's religious minorities - Ispahani, Farahnaz (New York, NY : Oxford University Press, 2017)
In Purifying the Land of the Pure, Farahnaz Ispahani analyzes Pakistan's policies towards its religious minority populations, both Muslim and non-Muslim, since independence in 1947.
Demography, state and religion -- Ideological state -- Militarism and national identity -- Balancing act : 1972-1977 -- Islamization : 1977-1988 -- Global jihad and Pakistan's minorities, 1988-1999 -- Militancy, terrorism and sectarianism - 1999 onwards.
Includes bibliographical references (pages 191-206) and index.
Keywords: Religious minorities -- Pakistan; Pakistan -- Politics and government -- 1971-1988.; Pakistan -- Politics and government -- 1988-